(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses the characteristics of the Internet and Internet relations. The author analyzes various theoretical approaches based on the systematization of paradigms in order to widen the concept of the internet.At the same time, this article examines the legal problems that have arisen with the advent of the Internet, in particular the legal status of the subjects of Internet relations and the cross-border nature of disputes arising in the context of interaction via the Internet.